Finiteness theorem for multi‐K‐bi‐Lipschitz equivalence of map germs. Issue 16 (27th June 2018) - Birbrair, Lev; Ferreira Costa, João Carlos; Da Silva Sena Filho, Edvalter; Mendes, Rodrigo
Abstract: Let P k ( n, p ) be the set of all real polynomial map germs f = ( f 1, ⋯, f p ) : ( R n, 0 ) → ( R p, 0 ) with degree of f 1, ⋯, f p less than or equal to k ∈ N . The main result of this paper shows that the set of equivalence classes of P k ( n, p ), with respect to multi‐ K ‐bi‐Lipschitz equivalence, is finite.